The Effect of the Hydrothermal Time and Temperature in the Synthesis to the Properties of Nitrogen-doped TiO2 - Misbah Rijal Ulhaq; Cahyorini Kusumawardani (Indonesian Journal of Chemistry and Environment, 2022)
Nitrogen-doped TiO2 (N-TiO2) has been synthesized through hydrothermal method by reacting the ethanolic solution of ethylene diamine with titanium precursor. The acidic contition was adjusted by the addition of glacial acetic acid. The hydrolysis process was done using hydrothermal process at various hydrothermal time and temperatures. The resulting materials were characterised FTIR, XRD, and Diffuse Refflectance UV/VIS Spectroscopy. The result showed that the increase of hydrothermal temperature lead to increase of particle size, but decreasing the band gap energy. However, the longer the hydrothermal time provided the decrease of particle size with no sugnificantly effect to the band gap energy.